2022
DOI: 10.4103/lungindia.lungindia_92_22
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glycopyrronium/formoterol delivered via a dry powder inhaler in patients with moderate to severe chronic obstructive pulmonary disease

Abstract: Background: We designed this randomised, open-label, parallel group, multi-centre study to investigate the efficacy and safety of glycopyrronium/formoterol, a long-acting muscarinic antagonist/long-acting β2-agonist fixed dose combination, delivered through a dry powder inhaler (DPI) in patients with chronic obstructive pulmonary disease (COPD). Material and Methods: We randomised (1:1) patients with moderate to severe COPD (N = 356) to receive glycopyrronium 25 µg/form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Multiple clinical trials have investigated the efficacy and safety of GFF combination therapy in patients diagnosed with COPD [ 14 ]. These studies have consistently demonstrated that GFF is comparable to tiotropium/formoterol (TFF) in enhancing lung function and assessing health status [ 12 , 13 ]. Moreover, GFF and TFF have exhibited favorable safety profiles and tolerability among symptomatic COPD patients [ 12 , 13 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple clinical trials have investigated the efficacy and safety of GFF combination therapy in patients diagnosed with COPD [ 14 ]. These studies have consistently demonstrated that GFF is comparable to tiotropium/formoterol (TFF) in enhancing lung function and assessing health status [ 12 , 13 ]. Moreover, GFF and TFF have exhibited favorable safety profiles and tolerability among symptomatic COPD patients [ 12 , 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…These studies have consistently demonstrated that GFF is comparable to tiotropium/formoterol (TFF) in enhancing lung function and assessing health status [ 12 , 13 ]. Moreover, GFF and TFF have exhibited favorable safety profiles and tolerability among symptomatic COPD patients [ 12 , 13 ]. In a comparative study evaluating twice-daily glycopyrronium/formoterol (GF) versus once-daily glycopyrronium (G), GF emerged as more effective in enhancing lung function and alleviating symptoms in individuals diagnosed with moderate-to-severe COPD [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations